FROM FICTION TO SCIENCE: HUMAN-ARTIFICIAL CO-INTELLIGENCE IN SCIENTIFIC RESEARCH AND EDUCATION (Interdisciplinary Studies Journal, 2025)
The article analyzes the use of generative artificial intelligence (GenAI), specifically ChatGPT and Copilot, in academic research, focusing on their application in qualitative data analysis. Through a case study titled “Choose the Apocalypse,” which explores scientific themes in science fiction works, the study evaluated the potential and limitations of these tools. Using a qualitative and descriptive approach, the research involved dialogues with GenAI to identify and classify scientific concepts present in the analyzed media. Results indicate that GenAI optimized tasks such as transcription, coding, and thematic analysis, enhancing efficiency and interpretative depth. However, challenges like “hallucinations” and limited recognition of specific works emerged, highlighting the need for rigorous human validation. The discussion emphasizes the benefits of human-artificial co-intelligence while warning of risks such as reduced critical thinking skills and threats to academic integrity. The study concludes that integrating GenAI with human expertise offers a promising path for scientific research and education, provided it is accompanied by critical use, ongoing validation, and attention to ethical considerations.
Keywords: Human-artificial co-intelligence; Science Education; AI hallucinations